Trace phenol-formaldehyde resin activation mechanism of intermediate graphitic layer removal in carbon for enhanced Li-ion capacitor performance - Xia, Yingkai; Wei, Shuang; Wei, Xiao; Chen, Yuehui; Ding, Jiahang; Zheng, Haoyuan; Yang, Sen; Yang, Shaobin (Frontiers in Chemistry, 2025)
Precise modulation of the pore structure in activated carbon can further enhance the capacitance performance of supercapacitors. As a carbonaceous precursor, phenol-formaldehyde resin (PR) plays a dual role in both carbon deposition and activation for pore regulation; however, the activation mechanism governing its pore-tuning effect remains unclear. In this study, trace PR with a mass ratio of 0.2%–0.8% was mixed with activated carbon for heat treatment. The results revealed that trace amounts of PR exhibit an activation mechanism by selectively removing intermediate graphene layers. Specifically, the removal of one–three graphene layers resulted in the formation of periodic micropores with diameters of 0.50–0.56 nm, 0.81–0.90 nm, and 1.14–1.19 nm. Correlation analysis demonstrated that the pore size most strongly associated with lithium-ion capacitance and diffusion coefficients fell within the range formed by the removal of a single graphene layer. Compared with one-step activation using PR, the multi-step activation process slowed the rate of pore expansion following single-layer removal, facilitating the formation of a greater proportion of 0.54 nm pores—those most closely linked to enhanced capacitance and ion diffusion. Consequently, the prepared coal-derived activated carbon achieved a capacitance of 164 F g-1, matching the highest reported values for aqueous lithium-ion capacitors using porous carbon (PC) materials. This study reveals a novel mechanism of precise pore modulation at the 0.01 nm scale through trace PR activation, providing new insights into the structural regulation of PC materials for advanced energy storage applications.